Ensino de espanhol para brasileiros : das crenças à prática docente - Vieira, Dark dos Santos (2012)
In recent years, we have observed that the presence of the Spanish language teaching in regular schools has been expanded gradually. However, even in the context of teaching-learning favoring of the Spanish language, it is quite frequently to hear from professionals in other fields and language learners that the broad similarity between Portuguese and Spanish facilitates communication among speakers of the two languages, and for that reason, Portuguese speakers would not need to devote themselves so deeply and systematically to the study of Spanish (or vice versa). In the field of Applied Linguistics around the same period, the number of researches focusing on beliefs related to the teaching-learning language process have increased and the results indicate the need for knowledge of teacher beliefs (trainers and training) so that one could achieve critical-reflexive education. From these findings, this ethnographic-based research developed under an interpretative perspective aims to investigate the perceptions and beliefs of Spanish teachers on the teaching of this language for Brazilians, and see how the relationship of the beliefs of these teachers with their context and their practice in the classroom is characterized. The participants of this survey were teachers of Spanish for Brazilians students in the metropolitan region of Campinas, São Paulo, and as instruments for data collection, we used a mixed questionnaire (with open questions and items in scale), interviews with teachers, field notes and recordings lessons in audio and video. This study took place on the basis of discussions on approaches to Teaching, teaching-learning language and beliefs. The data show us that, in general, the practice of teachers is guided by a system of beliefs and assumptions that underlie their approach to teaching. In addition, we also note that both beliefs about the approach of teaching have a strong relationship with the teaching context.